2002
DOI: 10.4161/cbt.51
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathogenesis of Rhabdomyosarcoma

Abstract: © 2 0 0 2 L a n d e s B i o s c i e n c e . N o t f o r d i s t r i b u t i o n .[Cancer Biology & ABSTRACTRhabdomyosarcoma (RMS) is a family of soft tissue tumors that are associated with the skeletal muscle lineage and generally occur in the pediatric population. Based on histopathologic features, two subtypes, embryonal (ERMS) and alveolar (ARMS), were identified and associated with distinct clinical characteristics and genetic alterations. ARMS is associated with 2;13 or 1;13 chromosomal translocations, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
172
0
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(180 citation statements)
references
References 77 publications
4
172
0
4
Order By: Relevance
“…Xia et al showed that MDM2 amplification events occur frequently in alveolar type, but only rarely in embryonal type. 27 In our study, of the three cases with MDM2 amplification, one case was alveolar type while two were embryonal type. MDM2 showed no association with the patients' prognoses or with any of the other clinicopathologic parameters, including histological type and age.…”
Section: Discussionmentioning
confidence: 49%
“…Xia et al showed that MDM2 amplification events occur frequently in alveolar type, but only rarely in embryonal type. 27 In our study, of the three cases with MDM2 amplification, one case was alveolar type while two were embryonal type. MDM2 showed no association with the patients' prognoses or with any of the other clinicopathologic parameters, including histological type and age.…”
Section: Discussionmentioning
confidence: 49%
“…These fusions alter the transactivation properties of the respective proteins and are thereby thought to contribute to carcinogenesis. The main evidence supporting this notion is that the Pax3-FOXO1 fusion protein is a more potent transcription activator than normal Pax3 protein in increasing the transcription of Pax3 target gene (Xia et al, 2002). The fusion protein is able to induce oncogenic transformation in cell culture (Scheidler et al, 1996;Kempf and Vogt, 1999;Xia and Barr, 2004), suggesting that the fusion protein may function as an oncogenic transcription factor by enhancing activation of normal PAX3 target genes.…”
Section: Foxo In Cancermentioning
confidence: 60%
“…The Banbury White Papers published in CSH Perspectives were devised as a framework for distilling these conclusions and disseminating them to the wider research community. distinct DNA methylation patterns, and extremely low sequence variation rates, as opposed to loss of heterozygosity at the 11p15.5 locus, frequent chromosomal gains, and a prominent role for RAS pathway activation in fusion-negative tumors (Xia et al 2002;Langenau et al 2007;Hettmer et al 2011;Chen et al 2013;Schneider et al 2014;Shern et al 2014).…”
Section: Box 1 the Banbury Center At Cold Spring Harbor Laboratorymentioning
confidence: 99%
“…Risk of treatment failure in pediatric RMS is stratified based on primary site, histology, and extent of disease. These stratification parameters do not currently include genotypic differences between fusion-positive and fusion-negative RMS or the full range of clinical, histological, and molecular variability seen across the RMS spectrum (Parham 2001;Xia et al 2002;Missiaglia et al 2012;Skapek et al 2013). …”
Section: Critical Clinical Problemsmentioning
confidence: 99%